Mechanical Stretch Triggers Epithelial-Mesenchymal Transition in Keratinocytes Through Piezo1 Channel - He, Jiahao; Shan, Shengzhou; Li, Qingfeng; Fang, Bin; Xie, Yun (Frontiers in Physiology, 2022)
The epithelial-mesenchymal transition (EMT) process has emerged as a central regulator of embryonic development, tissue repair and tumor malignancy. In recent years, researchers have specifically focused on how mechanical signals drive the EMT program in epithelial cells. However, how epithelial cells specifically leverage mechanical force to control the EMT process remains unclear. Here, we show that the bona fide mechanically activated cation channel Piezo1 plays a critical role in the EMT. The Piezo1 is expressed in human primary epidermal keratinocytes (HEKs) and is responsible for the mechanical stretch-induced Ca2+ concentration. Inhibition of Piezo1 activation by the inhibitor GsMTx4 or by siRNA-mediated Piezo1 knockdown influenced the morphology and migration of HEKs. Moreover, Piezo1 activity also altered EMT-correlated markers expression in response to mechanical stretch. We propose that the mechanically activated cation channel Piezo1 is an important determinant of mechanical force-induced EMT in keratinocytes and might play similar roles in other epithelial cells.